Maternal serum lactate dehydrogenase level as a predictor of adverse pregnancy outcome in women with severe preeclampsia - Awoyesuku, Peter A.; Ohaka, Chinweowa; Altraide, Basil O.; Amadi, Simeon C.; Iwo-Amah, Rose S.; Ngeri, Bapakaye; Jumbo, Awopola I. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2024)
Background: Preeclampsia is a multisystem disorder causing vascular endothelial damage and leads to leakage of lactate dehydrogenase (LDH) into maternal serum. This study evaluated the serum LDH levels in severe preeclamptic women to detect any correlation with adverse pregnancy outcomes. Methods: A prospective cohort study compared LDH levels of 68 severe preeclamptic women with 68 normotensives in the third trimester, matched for age, parity, and gestational age. The preeclamptic women were followed up until delivery to assess the maternal and neonatal outcomes. Data were analyzed with SPSS for Windows version 23. The level of significance was set at p<0.05. Results: Both groups were comparable in their characteristics. The mean LDH level for severe preeclamptic group (717.40 IU/L) was higher than for the normotensive group (162.90 IU/L) and this was significant (p=0.001). Cesarean delivery was less likely when LDH was >600 compared to ≤600 (OR 0.31; p=0.049) indicating a potential protective effect. The likelihood of IUGR (OR 3.14; p=0.045), IUFD (OR 6.48; p=0.028), stillbirth (OR 7.06 p=0.007), perinatal mortality (OR 4.84; p=0.004) and low birth weight <2500 gm (OR 3.77; p=0.025) were all significantly higher with LDH levels >600 IU/L. Conclusions: Maternal serum LDH levels were found to be significantly increased in pregnant women with severe preeclampsia compared to their normotensive counterparts, and elevated levels >600 IU/L in the third trimester was associated with adverse perinatal outcomes.